Peningkatan Hasil Belajar Bahasa Inggris dengan Penerapan Model Pembelajaran Kooperatif Time Token - Yartis Yartis (Pusat Riset dan Inovasi Nasional, 2022)
The purpose of this classroom action research is to implemen time token cooperative learning model to improve students' learning achievement of English through in VII 1 students of Semester I of MTsN 14 Tanah Datar in the 2022/ 2023 school year. This research was conducted in MTsN 14 Tanah Datarof class VII.1 as many as 32 students. This research is a Classroom Action Research conducted in two cycles. Data collection techniques used documentation, observation, and written tests. Data collection tools are observation sheets, test items, and value list documents. Data analysis using comparative descriptive analysis followed by reflection on each cycle consists of four steps, namely: (1) Planning, (2) Action Implementation, (3) observation, and (4) reflection. The results of this study indicate an increase in learning achievement of English students. The percentage of students' learning mastery, example before the action of 62,5%, in the first cycle of 75% and in the second cycle of 96,9%. In addition, average score of learning achievement of English students also experienced an increase before the action of 70,9, in the first cycle of 73,4 and on the second cycle of 81,7. So it can be concluded that